DOI: 10.26481/dis.20210903lj
|View full text |Cite
|
Sign up to set email alerts
|

Frisian on social media

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…From the age of the respondents, we can see that the respondents from late teenagers to young adults are the ones that participate the most. The young generations are digital natives, as they grew up surrounded by digital technologies, they are native speakers of the digital language of computers, video games, and also the Internet (Prensky, as cited in Jongbloed-Faber et al, 2016). We Are Social (wearesocial.com, in Ahmad and Nurhidaya, 2020) found that there was an increase in the use of social media compared to 2018 and its use was dominated by young people in Indonesia's generation Y (millennials) and Z, namely between 18-34 years old.…”
Section: Discussionmentioning
confidence: 99%
“…From the age of the respondents, we can see that the respondents from late teenagers to young adults are the ones that participate the most. The young generations are digital natives, as they grew up surrounded by digital technologies, they are native speakers of the digital language of computers, video games, and also the Internet (Prensky, as cited in Jongbloed-Faber et al, 2016). We Are Social (wearesocial.com, in Ahmad and Nurhidaya, 2020) found that there was an increase in the use of social media compared to 2018 and its use was dominated by young people in Indonesia's generation Y (millennials) and Z, namely between 18-34 years old.…”
Section: Discussionmentioning
confidence: 99%
“…It is still unclear what the impact of these family attitudes might be on the linguistic development and language use of these pupils. However, some studies have shown that attitudes towards different languages and multilingualism more generally condition the use and time distribution that multilingual individuals make of their languages [13].…”
Section: Introductionmentioning
confidence: 99%